HILIRISASI INDUSTRI SAWIT DI SUMATERA UTARA - Matupalesa, Andi; Nauly, Yudhi Dharma; Fanani, Ivan (Politeknik Keuangan Negara STAN, 2019)
This study aims to provide an overview of the potential downstream of the palm oil industry in North Sumatra, by conducting a series of visits to companies that act as an anchors in the palm oil industry, particularly those located in KEK Sei Mangkei, Kuala Tanjung and KIM. The writing of this study was conducted by using descriptive-explorative analysis method which relies on primary data from companies considered to have a key role in palm industry in North Sumatra. The research method used in the form of identification of value chain, hub-and-spoke and assess the value added of the downstream stages of palm oil. In the end, the downstream of palm oil industry also needs to prioritize the role of anchor companies as locomotives for palm oil industry development in the future.